The Relative Bioavailability of Ibuprofen After Administration With a Novel Soft Chewable Drug Formulation. Issue 2 (25th April 2017) - Hattrem, Magnus N.; Dille, Morten J.; Seternes, Tore; Ege, Thorfinn; Draget, Kurt I.
Abstract: The first aim of the present study was to evaluate the bioavailability of ibuprofen dispersed in a novel soft chewable formulation compared with a traditional ibuprofen tablet; its second was to map the quality of taste masking and patient product satisfaction. In a phase 1, single‐center, open‐label, randomized, crossover study, healthy subjects received a soft‐chew formulation or a hard tablet (reference), both containing 100 mg ibuprofen. Serial blood samples were collected over 24 hours to assess ibuprofen bioavailability. Taste and satisfaction after chewing the novel formulation 3 or 8 times were evaluated with a questionnaire. The soft‐chew formulation showed comparable bioavailability to the reference tablet. The highest peak plasma concentration was observed after 3 chews, and the relative bioavailability was approximately 8% higher compared to 8 chews. The overall flavor was well appreciated, and chewing 3 times was significantly preferred ( P = .043) over chewing 8 times. Soft chewable drug formulations may improve compliance and potentially benefit several subpopulations who experience dysphagia.